Physical Education of Students in Higher Education Institution on the Basis of Volleyball - Abduvakhit Akhatovich Karimov; Abdusamad Akhatovich Karimov (Universitas Muhammadiyah Sidoarjo, 2022)
The article talks about the problems of increasing the efficiency of teaching students the technique of volleyball in the process of physical education. The severity of this problem is even more intensified if we take into account that volleyball is distinguished by a wide variety of techniques, and the time allocated for its study in the process of physical education at a university is limited.